Diasporic dis/location: a study of the themes of memory, home and homecoming in The Namesake, Desirable Daughters and Beloved Strangers: A Memoir - Shahid, Tasnim (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2016.